2004
DOI: 10.1108/01437720410536007
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction and gender: an expanded specification from the NLSY

Abstract: Estimates the determinants of job satisfaction for younger US workers. While age representative data from both the USA and Britain routinely show women reporting greater job satisfaction, this is not true for the younger US cohort in National Longitudinal Survey of Youth sample. Finds no gender satisfaction gap, but does find that the job satisfaction of women is less sensitive to both actual and comparison earnings than that of men. Moreover, estimates an expanded specification showing substantial gender diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
3
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(83 citation statements)
references
References 29 publications
7
69
3
4
Order By: Relevance
“…Souza-Poza and Sousa-Poza (2003) undertook a meta-analysis in Britain using 1991-2000 data and found evidence of falling levels of job satisfaction among females over time. Similar to Clark's (1997) as well as Sloane and William's (2000) findings, Donohue and Heywood (2004) found no gender job satisfaction gap for young United States workers, once again indicating that specific female labor market groups possess expectation levels similar to those of their male counterparts.…”
Section: International Journal Of Research Studies In Education 73supporting
confidence: 62%
“…Souza-Poza and Sousa-Poza (2003) undertook a meta-analysis in Britain using 1991-2000 data and found evidence of falling levels of job satisfaction among females over time. Similar to Clark's (1997) as well as Sloane and William's (2000) findings, Donohue and Heywood (2004) found no gender job satisfaction gap for young United States workers, once again indicating that specific female labor market groups possess expectation levels similar to those of their male counterparts.…”
Section: International Journal Of Research Studies In Education 73supporting
confidence: 62%
“…Artz (2008) and Donohue and Heywood (2004) found that bonus in fringe benefits do not significantly impact job satisfaction in cross-section estimates. Yet Bender (2005), Heywood and Wei (2006) and Bender and Heywood (2006) found that fringe benefits positively impact job satisfaction in cross-section estimates.…”
Section: The Link Between Organizational Rewards and Employees' Satismentioning
confidence: 99%
“…However, differences often disappear when a number of other variables are controlled (Oshagbemi 2003). For example, Donohue and Heywood (2004) were not able to find gaps in gender satisfaction when focusing on a younger US cohort and using data from the National Longitudinal Survey of Youth. As a methodological point, the authors also stress the importance of dividing samples by gender and by occupational group.…”
Section: Empirical Analysis With European Datamentioning
confidence: 99%